Platelet hyperreactivity and frailty in a mouse model of Alzheimer’s disease are prevented by anti-oxidant treatment - Mauro Vismara; Silvia Maria Grazia Trivigno; Marta Zarà; Stefania Momi; Paolo Gresele; Marina Camera; Ilaria Canobbio; Gianni Francesco Guidetti; Mauro Torti (GeroScience, 2025)
Frailty is an age-related syndrome commonly associated with different comorbidities, and its occurrence is particularly frequent in patients with Alzheimer’s disease (AD). A persisting low-grade inflammation has been suggested to favor the onset of both AD and frailty. Besides their role in hemostasis and thrombosis, blood platelets are true inflammatory cells, and their direct contribution to the onset and progression of AD has been documented. In this work, we investigated whether platelet hyperreactivity and pro-oxidative functions are implicated in the development of frailty in a mouse model of AD, the APP23 mice. Assessment of 31 specific clinical signs of deterioration in mice at 3, 9, and 18 months of age demonstrated that the development of frailty was significantly more pronounced in the APP23 mice compared to wild-type littermates. In 18-month-old APP23 mice, a significant platelet hyperreactivity was detected as shown by a significantly stronger platelet aggregation in response to submaximal stimulation of both collagen and thrombin receptors. Moreover, the pro-inflammatory function of platelets, evaluated as circulating and agonist-induced platelet-neutrophil aggregate formation, was significantly increased in aged APP23 mice compared to wild-type littermates. Platelet hyperreactivity was partially prevented by prolonged treatment with the anti-oxidant agent Tempol, which reduced both agonist-induced aggregation and platelet-neutrophil aggregate formation. Importantly, prolonged treatment of APP23 mice with Tempol significantly reduced also the frailty index score in 18-month-old animals. These results outline the possible beneficial effect of an anti-oxidant treatment in hampering platelet hyperreactivity and preventing the onset of frailty associated to AD.

Serum from COVID-19 patients promotes endothelial cell dysfunction through protease-activated receptor 2 - Francesco Vieceli Dalla Sega; Francesca Fortini; Danilo Licastro; Simeone Dal Monego; Margherita Degasperi; Alessia Ascierto; Luisa Marracino; Paolo Severi; Maria D’Accolti; Irene Soffritti; Marta Brambilla; Marina Camera; et al. (Inflammation Research, 2024)

Cerebral derailment after myocardial infarct: mechanisms and effects of the signaling from the ischemic heart to brain - Paolo Gelosa; Laura Castiglioni; Joanna Rzemieniec; Majeda Muluhie; Marina Camera; Luigi Sironi (Journal of Molecular Medicine, 2022)
Myocardial infarction (MI) is the leading cause of death among ischemic heart diseases and is associated with several long-term cardiovascular complications, such as angina, re-infarction, arrhythmias, and heart failure. However, MI is frequently accompanied by non-cardiovascular multiple comorbidities, including brain disorders such as stroke, anxiety, depression, and cognitive impairment. Accumulating experimental and clinical evidence suggests a causal relationship between MI and stroke, but the precise underlying mechanisms have not yet been elucidated. Indeed, the risk of stroke remains a current challenge in patients with MI, in spite of the improvement of medical treatment among this patient population has reduced the risk of stroke. In this review, the effects of the signaling from the ischemic heart to the brain, such as neuroinflammation, neuronal apoptosis, and neurogenesis, and the possible actors mediating these effects, such as systemic inflammation, immunoresponse, extracellular vesicles, and microRNAs, are discussed.